THE LEVEL OF ACCEPTANCE TOWARDS INTERRACIAL MARRIAGE AMONG MALAYSIAN - Nor Hafizam, Erie Nur Fatihah; Ridzuan, Abdul Rauf; Abdul Ghafar, Nur Alia Elyna; Abdul Haqq, Maisarah Azani Fadli; Mohd Azizi, Muhammad Afiq Irfan; Prawira, Indra; Yahaya , Fatimah Yazmin (I-iECONS e-proceedings, 2023)
The world now is bound to be more different compared to 50 years ago. While there is a modest rise in number of people who choose to marry spouses from different ethnic group in the country, the practice itself has been generally portrayed as a problematic and wanting especially in the Peninsular Malaysia. This study is conducted to investigate the level of acceptance towards interracial marriage. Many believe that interracial marriage has a potential to create tensions between the spouses due to their differences in ethnic background and culture. Based on our quantitative study conducted on 308 respondents, many still doubt the effectiveness of this inter-ethnic marriage making them to be averse on this issue.. This study is applying a method of quantitative research, by answering a short survey consisted of 27 questions. Based on the findings, The overall mean of the level of acceptance of interracial marriage is high (M=3.25), and the overall mean of the understanding of interracial marriage is high (M=3.26). This shows that interracial marriage is being accepted in Malaysia.